The Development of Literature Learning Achievement of Grade 6 Students: Exploring ‘Khun Chang Khun Phan’ in Its ‘Birth His Plai-Ngam’ Chapter through a Flipped Classroom Approach Utilizing the CIRC Technique - Suwanpanich, Supranan; Pengpoom, Brapaas (Ratchaphruek Journal, 2024)
This research aims to develop the literature learning achievement of grade 6 students by exploring ‘Khun Chang Khun Phan’ in its ‘Birth of Plai-Ngam’ chapter through a Flipped Classroom approach utilizing the CIRC technique. The objectives are: 1) to develop a literature learning management plan, 2) to compare the learning outcomes of literature for grade 6 students, and 3) to evaluate the satisfaction of grade 6 students towards literature learning management. The sample group consisted of 11 grade 6 students from Wat Khong Karam School, Primary Education Area Office, Phichit District 2, Academic Year 2023, selected by purposive sampling. The research tools used include: 1) a literature learning management plan, 2) a test measuring the learning outcomes of literature, and 3) a questionnaire measuring the satisfaction of grade 6 students towards literature learning management. Statistical analyses utilized include mean, standard deviation, and dependent t-test. Research findings indicate that: 1) The appropriateness of the components of the literature learning management plan yielded significantly high results ( = 4.34, S.D. = 0.61), 2) The achievement of grade 6 students on pre- and post-learning tests showed average scores of 11.64 and 25.27 respectively, with a statistical significance of .05, and 3) Grade 6 students expressed the highest overall satisfaction ( = 4.79, S.D. = 0.10)